PENDIDIKAN ISLAM DAN PERUBAHAN-PERUBAHAN SOSIAL - Muhammad Fathurrohman (Ulumuna: Jurnal Studi Keilsman, 2015)
Islam as a religion in the world that rahmatan lil 'alamin lowered to bring change to the community. One of the changes is through Islamic education. Islamic education from birth experienced various ups and downs of development, ranging from the golden age, a period of stagnation and development of the synchronization and integration of Islamic education with modern education. Social change in a Muslim society is usually indicated by the development of civilization in the Muslim community. So the conclusion can be drawn that the substance of social change is the emergence of a strong Muslim civilization